Peningkatan Kinerja Bidang Kesehatan, Motivasi dan Pelayanan Prima - Madiistriyatno, Harries; Setiawan, Adi (Ridwan Institute, 2021)
The purpose of this study is anything to know how big the appearance of the field of health, pelitif and excellent service This research method of descriptive statistical analysis in a double way double with the method of double pardigma two free variables and one variable variable. each variable is a promise, the 33rd relationship, one by one or good. analysis of which analysis between analysis variables with Health Field Performance may be Y= 47.215+ 0.123X2 and double regression related between variables and excellent service together with health field performance again Y= 27.594+ 0.370 X1+ 0.127X2. From the results of this study, there is an influence between the capabilities of the health sector in puskesmas which is linked to the research hypothesis, namely there is an influence between the health sector and the health sector, there is the influence of excellent services with the field of health, and there is the influence of excellent capabilities and services together with the field of health in the Tanjungsari Health Center Bogor Regency.